And, finally, take your decision - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Decision Tools for Sustainable Development. By I F Grant and C Sears. Natural Resources Institute. 1999. 281 pp. ISBN 0 85954 500 8 Order number ECN12 GBP 18 Euro 30.05